Comparison of Kangaroo Mother Care with Conventional Care in Newborns in Terms of Frequency of Successful First Breastfeeding and Time to Initiate Breast Feeding - Iqbal, Amjad; Iqbal, Tehreem; Bashir, Faisal; ., Bilqees; Aslam, Shahid; Anjum, Sehrish (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare kangaroo mother care with conventional care in newborns regarding the frequency of successful first breastfeeding and time to initiate breastfeeding.Study Design: Quasi-experimental study.Place and Duration of Study: Departments of Pediatrics and obstetrics CMH Bahawalpur from Feb 2019 to Jun 2020.Methodology: 120 infant-mother couples were included in the study. Sixty infant-mother couples were randomly allocated to each group (120 infants). Group A was nursed with kangaroo mother care (KMC), and Group B was nursed with conventional care (CC). The frequency of the first successful feed was assessed, and the time taken to initiate breastfeeding was documented.Results: There was no statistically significant difference in weight, gestational age and gender distribution between the two groups. 65 (54.25%) infants had successful first breastfeeding in the study population. 38 (63.3%) of the infants had first successful breastfeeding as per the Infant Breast feeding Assessment Tool (IBFAT) in group A (KMC) as compared to 27 (45%) in group B (Conventional Care). The difference between the two groups was statistically significant, with a p-value of 0.044. Mean time for first successful breastfeeding was significantly less for the KMC group as compared to the conventional group with a p-value of